Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Etnomatematika Budaya Minangkabau Pada Materi Kekongruenan dan Kesebangunan - Isnaniah Isnaniah; Pipit Firmanto; M. Imamuddin (Mathematics Education Study Program, 2023)
This is motivated by the fact that there is no learning media based on Minangkabau culture in learning mathematics. This study aims to determine the validity, practicality and effectiveness of ethnomathematics-based Student Worksheets (LKPD) in Minangkabau culture on the material of congruence and congruence. The type of research used is Research & Development (R & D). The LKPD was developed based on the Plomp and Nieveen Model with 3 phases, namely: 1) preliminary research, 2) development or prototyping phase and 3) assessment phase. The formative valuations such as: self evaluation, expert review, one to one evaluation, small group and field tests, carried out in an integrated manner during the design phase. Data was collected through interviews, validation sheets, questionnaires and tests. The results showed: 1) Ethnomatematics-based LKPD validity obtained a percentage of 92% with a very valid category, 2) Practicality of LKPD in one to evaluation obtained a percentage of 90% with a very practical category, in the small group obtained a percentage of 95% with a very practical category. 3) The effectiveness of student worksheets seen from the results of students' mathematics learning, obtained student mastery of 86.7% with very effective criteria. The developed LKPD can be used in learning mathematics. Learning by involving Minangkabau culture can improve learning outcomes and develop and build student character. Based on the results of this study, educators are expected to develop teaching materials that are associated with local culture or the culture where students live. Once developed, then used in learning mathematics.